Live-cell single-molecule tracking highlights requirements for stable Smc5/6 chromatin association in vivo - Etheridge, Thomas J; Villahermosa, Desiree; Campillo-Funollet, Eduard; Herbert, Alex David; Irmisch, Anja; Watson, Adam T; Dang, Hung Q; Osborne, Mark A; Oliver, Antony W; Carr, Antony M; Murray, Johanne M (eLife, 2021)
The essential Smc5/6 complex is required in response to replication stress and is best known for ensuring the fidelity of homologous recombination. Using single-molecule tracking in live fission yeast to investigate Smc5/6 chromatin association, we show that Smc5/6 is chromatin associated in unchallenged cells and this depends on the non-SMC protein Nse6. We define a minimum of two Nse6-dependent sub-pathways, one of which requires the BRCT-domain protein Brc1. Using defined mutants in genes encoding the core Smc5/6 complex subunits, we show that the Nse3 double-stranded DNA binding activity and the arginine fingers of the two Smc5/6 ATPase binding sites are critical for chromatin association. Interestingly, disrupting the single-stranded DNA (ssDNA) binding activity at the hinge region does not prevent chromatin association but leads to elevated levels of gross chromosomal rearrangements during replication restart. This is consistent with a downstream function for ssDNA binding in regulating homologous recombination.